2012
DOI: 10.23846/sr0017
|View full text |Cite
|
Sign up to set email alerts
|

Water, sanitation and hygiene interventions to combat childhood diarrhoea in developing countries

Abstract: The International Initiative for Impact Evaluation (3ie) is an international grant-making NGO promoting evidence-informed development policies and programmes. We are the global leader in funding, producing and synthesising high-quality evidence of what works, for whom, how, why and at what cost. We believe that using better and policy-relevant evidence helps to make development more effective and improve people's lives. 3ie systematic reviews 3ie systematic reviews appraise and synthesise the available high-qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
233
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(240 citation statements)
references
References 42 publications
5
233
0
2
Order By: Relevance
“…3 A 36 percentage point increase in detection of free chlorine in combined WASH arms compared with the control group and a 60 percentage point increase in the water-only treatment arms are both significant improvements over the status quo. The 17 percentage point reduction in visible stool in the latrine coupled with the 55 percentage point increase in drop holes being covered show that the sanitation interventions were also successfully adopted in the combined WASH arms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 A 36 percentage point increase in detection of free chlorine in combined WASH arms compared with the control group and a 60 percentage point increase in the water-only treatment arms are both significant improvements over the status quo. The 17 percentage point reduction in visible stool in the latrine coupled with the 55 percentage point increase in drop holes being covered show that the sanitation interventions were also successfully adopted in the combined WASH arms.…”
Section: Discussionmentioning
confidence: 99%
“…1 Water, sanitation, and hygiene (WASH) interventions have been found to reduce diarrheal and respiratory diseases among children, but conclusive evidence on the relative health benefits of these interventions is lacking. 2 Furthermore, few studies have evaluated these interventions in combination to assess how benefits might aggregate, 3 and few studies have been able to measure objective health outcomes instead of caregiver-reported outcomes. 4 The main WASH Benefits study (http://www.washbenefits .net), a multiarm, cluster, randomized, controlled trial presently being conducted in both Bangladesh and Kenya, is designed to address many of the shortcomings just described.…”
Section: Introductionmentioning
confidence: 99%
“…For example the systemic reviews to assess the impact of inadequate water and sanitation on diarrhoeal disease in low and middleincome settings have shown that overall improvements in drinking water and sanitation were associated with decreased risks of diarrhoea. However greater reductions in diarrhoea were seen with interventions as the use of water filters, provision of high-quality piped water and sewer connections (Fink, GĂŒnther, and Hill 2011;Kumar and Vollmer 2012;Wolf et al 2014) (Waddington et al 2009). In another randomized controlled trial experiment in urban Morocco the study suggested that improved water infrastructure did not improve the water quality and health benefit rather improved the time saving and intra-household conflict (Devoto et al 2011).…”
Section: Watsan Infrastructure Water Quality and Impact On Healthmentioning
confidence: 99%
“…Yet, despite decades of extensive efforts to develop and promote an assortment of HWT products, achieving the sustained adoption and consistent use of HWT remains extremely challenging. 5,6 The most commonly used HWT method by far is boiling, with an estimated 1.2 billion users globally. 7−9 Boiling is straightforward to use, does not substantially change the taste of the water, and can provide complete pathogen inactivation (regardless of pathogen types or water turbidity).…”
Section: Introduction and Objectivesmentioning
confidence: 99%